Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
[tex]\frac{9}{10}^{(3}-\frac{1}{15}^{(2}= \frac{27-2}{30}= \boxed{\frac{25}{30}=\frac{5}{6}}[/tex]
[tex] \frac{9}{10}- \frac{1}{15}= \frac{9*3}{10*3}- \frac{2}{15*2} = \frac{27}{30}- \frac{2}{30} = \frac{25}{30}= \frac{5}{6} [/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.